Towards Sustainable Environmental Quality: Priority Research Questions for the Australasian Region of Oceania. (13th September 2019) - Gaw, Sally; Harford, Andrew; Pettigrove, Vincent; Sevicke‐Jones, Graham; Manning, Therese; Ataria, James; Cresswell, Tom; Dafforn, Katherine A; Leusch, Frederic DL; Moggridge, Bradley; Cameron, Marcus; Chapman, John; et al.
ABSTRACT: Environmental challenges persist across the world, including the Australasian region of Oceania, where biodiversity hotspots and unique ecosystems such as the Great Barrier Reef are common. These systems are routinely affected by multiple stressors from anthropogenic activities, and increasingly influenced by global megatrends (e.g., the food–energy–water nexus, demographic transitions to cities) and climate change. Here we report priority research questions from the Global Horizon Scanning Project, which aimed to identify, prioritize, and advance environmental quality research needs from an Australasian perspective, within a global context. We employed a transparent and inclusive process of soliciting key questions from Australasian members of the Society of Environmental Toxicology and Chemistry. Following submission of 78 questions, 20 priority research questions were identified during an expert workshop in Nelson, New Zealand. These research questions covered a range of issues of global relevance, including research needed to more closely integrate ecotoxicology and ecology for the protection of ecosystems, increase flexibility for prioritizing chemical substances currently in commerce, understand the impacts of complex mixtures and multiple stressors, and define environmental quality and ecosystem integrity of temporary waters. Some questions have specific relevance to Australasia, particularly the uncertainties associated with using toxicity data from exotic species to protect unique indigenous species. Several related priority questions deal with the theme of how widely international ecotoxicological data and databases can be applied to regional ecosystems. Other timely questions, which focus on improving predictive chemistry and toxicology tools and techniques, will be important to answer several of the priority questions identified here. Another important question raised was how to protect local cultural and social values and maintain indigenous engagement during problem formulation and identification of ecosystem protection goals. Addressing these questions will be challenging, but doing so promises to advance environmental sustainability in Oceania and globally. Key Points: The first process to identify priority research questions for the Australasian region of Oceania. Priority areas identified included integration of ecology and ecotoxicology, impacts of multiple stressors, and using data from exotic species to protect indigenous species. The need to protect local cultural and social values and maintain indigenous peoples' engagement during problem formulation and identification of ecosystem protection goals was also highlighted.